The Effect of Financial Literacy, Financial Inclusion, Financial Technology Towards Financial Performance of Micro Business (Case study of micro waqf bank customers at As'ad Islamic Boarding School, Jambi City) - Dhea Indah Arum Sari; Sri Rahayu; Muhammad Ridwan (PT FORMOSA CENDEKIA GLOBAL, 2023)
The aim of this research is to investigate how financial literacy, financial inclusion, and financial technology influence the financial performance of micro-enterprises.A sample of 68 respondents was randomly selected for data analysis through a questionnaire. The hypotheses were tested using the multiple linear regression analysis method with the assistance of SPSS For Window Version 25 software. The findings indicate that financial literacy, financial inclusion, and financial technology significantly influence the financial performance of micro-enterprises. Specifically, financial literacy positively affects the financial performance of micro-enterprises, while financial inclusion does not have a significant impact. Additionally, financial technology positively influences the financial performance of micro-businesses